Motivating Knowledge Sharing: A Pathway to Enhanced Nurse Performance - Ismiatun, Ismiatun; Khajar, Ibnu (Universitas Semarang, 2025)
This study investigated the influence of work motivation and knowleldge sharing on employee performance within the healthcare sector, specifically among nursing staff at RSUD dr Gondo Suwarno. The research aimed to explore the direct and indirect effects of these variables, with job satisfaction serving as a mediating factor. Data was collected through a quantitative survey involving 149 nursing staff, and structural equation modeling (SEM) was employes to analyze the relationships. The findings revaled that work motivation did directly impact employee performance, and it positively influenced job satisfaction. Conversely, knowledge sharing demonstrated a significant positive relationship with both job satisfaction and employee performance. Moreover, job satisfaction emerged as a crucial mediator, amplifying the positive effects of both work motivation and knowledge sharing on employee performance. These reseults underscore the importance of holostic human resource management strategies that prioritize employee satisfaction. Organixation are encouraged to create supportive work environments that foster motivation, facilitate knowledge sharing, and offer opportunities for career development. Future research could delve deeper into the dynamic of these relationships within diverse organizational contexts